PEMANFAATAN HUJAN DALAM AL-QUR’AN: SEBUAH TAFSIR SAINTIFIK - Irfan Rizky Maulana; Anisah Dwi Lathifah; Wildan Akhmad Syauqi; Awalia Khalifatur Riska; Asma Laili Hanifah; Catur Sri Lestari; Aldiansyah Aldiansyah (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2024)
Rain is an important natural phenomenon in human life on earth. Allah created everything in the heavens and the earth and between them with His majesty and glory. One sign of His power is rain which can benefit the lives of living creatures on earth. This paper examines the use of rain in the Al-Qur'an. This research uses qualitative methods with the type of literature study. Data will be obtained through reviewing information and knowledge from various relevant literature and references as well as analyzing interpretations of Al-Qur'an verses. How rain is a natural phenomenon that is essential for human life, where water is one of the great precious blessings from God. The research results show that the Al-Qur'an provide information about the use of rain in various aspects of human life, such as agriculture, animal husbandry, and in everyday life.